2023
DOI: 10.1101/2023.11.15.23298565
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hematologic abnormalities after COVID-19 vaccination: A large Korean population-based cohort study

Hye Sook Choi,
Min-Ho Kim,
Myeong Geun Choi
et al.

Abstract: Adverse hematologic events have been reported after COVID-19 vaccination. The objective of this study was to investigate whether hematologic abnormalities develop after COVID-19 vaccination. Retrospective cohort analyses of data from the Korean National Health Insurance Service (KNHIS) database were conducted from July 2022 to August 2023. We randomly selected data of half of those living in Seoul City as of January 1, 2021 with their diagnostic records up to December 31, 2021. The included participants were v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
(71 reference statements)
0
1
0
Order By: Relevance
“…Furthermore, not having pre-infection hemoglobin data makes evaluating acute changes impossible. In addition, it has been shown that vaccination against SARS-CoV-2 might enhance the likelihood of hematologic problems, such as anemia [ 59 ] and on the other hand, that receiving the vaccine prior to SARS-CoV-2 infection might be associated with a lower risk of developing Long-COVID [ 60 ]. However, since the vaccination pattern varied greatly ( Tables S6 and S7 ) and our sample size was not large enough, we were unable to analyze the association between anemia and vaccination status in our population.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, not having pre-infection hemoglobin data makes evaluating acute changes impossible. In addition, it has been shown that vaccination against SARS-CoV-2 might enhance the likelihood of hematologic problems, such as anemia [ 59 ] and on the other hand, that receiving the vaccine prior to SARS-CoV-2 infection might be associated with a lower risk of developing Long-COVID [ 60 ]. However, since the vaccination pattern varied greatly ( Tables S6 and S7 ) and our sample size was not large enough, we were unable to analyze the association between anemia and vaccination status in our population.…”
Section: Discussionmentioning
confidence: 99%